Existence and Uniqueness Results for Singular Boundary Value Problem of Weighted Generalized Fisher Type Differential Equation - Benkaci-Ali, Nadir (IndoMS, 2021)
In this paper, we give existence and uniqueness results of nontrivial positive solution for the boundary value problem of the weighted and generalized Fisher's type differential equation.